2011
DOI: 10.1007/s10641-011-9816-0
|View full text |Cite
|
Sign up to set email alerts
|

Length-based growth, maturity and natural mortality of the cockfish Callorhinchus callorhynchus (Linnaeus, 1758) off Coquimbo, Chile

Abstract: The growth rate, reproductive aspects, and natural mortality of chimaeras and ratfish are poorly known. In this study, life-history parameters for cockfish Callorhinchus callorhynchus (Holocephali-Callorhinchidae) are estimated, which is an important fish resource exploited in Chile. Specimens were sampled from the artisanal fishery captures, from November 2006 to November 2007. The standard length (SL) of males fluctuated between 20 and 62 cm, and between 21 and 70 cm for females. Von Bertalanffy growth param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
2
7
0
12
Order By: Relevance
“…The PCL 50 estimated for females in this study (466.22 mm; n=167) was similar to that recently obtained in northern Patagonian waters (474.80 mm; n=398) (Bernasconi et al, 2015b) but smaller than those previously reported in that zone (490 mm; n=123) (Di Giácomo, Perier, 1994) and in Chilean waters (500 mm; n=40) (Alarcón et al, 2011). These differences may be attributable to differences in the methods for assessing maturity and/or in sample size used in each study.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The PCL 50 estimated for females in this study (466.22 mm; n=167) was similar to that recently obtained in northern Patagonian waters (474.80 mm; n=398) (Bernasconi et al, 2015b) but smaller than those previously reported in that zone (490 mm; n=123) (Di Giácomo, Perier, 1994) and in Chilean waters (500 mm; n=40) (Alarcón et al, 2011). These differences may be attributable to differences in the methods for assessing maturity and/or in sample size used in each study.…”
Section: Discussionsupporting
confidence: 85%
“…Sexual size dimorphism is also a common characteristic observed in other holocephalans, with females larger than males (Freer, Griffiths, 1993;Francis, 1997;Nibam, 2011;Bell, 2012). The same pattern was observed for C. callorynchus in northern Patagonian waters (PCL males=620 mm; PCL females=760 mm) and in Chilean waters (PCL males=620 mm; PCL females=700 mm) (Di Giácomo, 1992;Alarcón et al, 2011;Bernasconi et al, 2015b). The differences in maximum size among studies for males (present study: n=19; northern Patagonian waters: n=147; Chilean waters: n=193) and females (present study: n=167; northern Patagonia waters: n =1571; Chilean waters: n=209) may result from differences in sample sizes.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations